Insecurity in the Middle East: Why Do the Reformist Movements Constantly Fail? Towards a New Conceptual Framework - Dolatabadi, Ali Bagheri; Shafie Seifabadi, Mohsen (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
Over the last three decades, the Middle East countries have frequently witnessed popular protests against the authoritarian regimes. The question is why these protests never come to a desirable end? Regardless of the role played by foreign actors in perpetuating the authoritarian regimes of the Middle East, it seems that what causes the protests not to be pervasive and the political infrastructures not to collapse is that the protests have not been supported by the people’s majority. The present article argues that such a dearth of support refers to a fundamental cause that we named the fear cycle. This cycle includes the masses’ fear of the regime, fear of the movement’s failure and its dire consequences, and fear of the political system that is supposed to come to power after the overthrow of the incumbent government. The governments have an important role in creating and perpetuating this fear and turning it into a panic.

W ciągu ostatnich trzech dekad kraje Bliskiego Wschodu często były świadkami powszechnych protestów przeciwko reżimom autorytarnym. Pytanie brzmi, dlaczego te protesty nigdy nie przynoszą pożądanego rezultatu? Niezależnie od roli, jaką odgrywają podmioty zagraniczne w utrwalaniu autorytarnych reżimów na Bliskim Wschodzie, wydaje się, że tym, co powoduje, że protesty nie są wszechobecne, a infrastruktury polityczne nie upadają, jest fakt, że protesty nie zostały poparte przez większość narodu. W niniejszym artykule dowodzimy, że taki brak poparcia związany jest z fundamentalną przyczyną, którą nazwaliśmy cyklem strachu. Cykl ten obejmuje strach mas przed reżimem, strach przed porażką ruchu i jej strasznymi konsekwencjami oraz strach przed systemem politycznym, który ma dojść do władzy po obaleniu urzędującego rządu. Ważną rolę w tworzeniu i utrwalaniu tego strachu oraz przekształcaniu go w panikę pełnią rządy.
Brak bezpieczeństwa na Bliskim Wschodzie: Dlaczego ruchy reformatorskie stale ponoszą porażkę? W kierunku nowych ram teoretycznych
Keywords: The Middle East; Political Protests; Fear; Insecurity; Authoritarian Regimes; Bliski Wschód; protesty polityczne; strach; brak bezpieczeństwa; reżimy autorytarne